Management of Innovation in Network Industries The Mobile Internet in Japan and Europe - Haas, Michael (Deutscher Universitätsverlag : Imprint: Deutscher Universitätsverlag, 2006)
Mobile Internet services are a tremendous success in Japan, but fail to gain the acceptance of European customers. Which factors explain the Japanese success story? What makes the difference: demand side factors rooted in a different culture or the fact that Japanese firms manage innovation process differently than their European counterparts? Drawing on a comparative case study Michael Haas analyses the consequences of differences in the innovation strategies of Japanese and European telecommunication firms. He focuses on the following questions: Which are the implications of different approaches towards management of systemic innovations? Do differences matter and why do they matter? The author shows that Europeans can learn from the Japanese and gives advice for future approaches to developments in the European telecommunications industry.